PENGARUH KARAKTERISTIK AUDITOR TERHADAP KUALITAS HASIL PEMERIKSAAN BPK RI PUSAT - RATU SIFA NI’MAH; DINI MARTINDA LESTARI (AKADEMIKA, 2019)
This study aims to determine the effect of the characteristics of the auditors on the quality of the results of BPK RI. Characteristics auditor is professionalism, accountability, integrity, objectivity, work experience, independence, competence, and skepticism, in which an examiner should be guided by SPKN, SPAP, and the code of ethics for the State financial inspection. The study population was the BPK Audit Center with the criteria that the auditor has to follow the Education and Training Functional Examination (JFP). Research data analysis using multiple linear regression. The results showed that the objectivity and competence do not affect the quality of the examination results. While variable professionalism, accountability, integrity, work experience, independence and skepticism affects the quality of test results produced by the examiner on the BPK Center.